Comparison of maternal and neonatal outcomes from full-dilatation cesarean deliveries using the Fetal Pillow or hand-push method. Issue 3 (December 2016) - Safa, Huda; Beckmann, Michael
Abstract: Objective: To compare maternal and neonatal outcomes of full-dilatation cesarean deliveries using the Fetal Pillow or hand- push method. Methods: A retrospective cohort study included data from all women who underwent full-dilatation cesarean deliveries at term that involved the use of the Fetal Pillow or the hand-push method at Mater Mothers' Hospital, Brisbane, Australia between May 1, 2013 and March 31, 2015. Maternal (estimated blood loss, need for blood transfusion, uterine angle extension, and duration of stay in hospital following delivery) and neonatal outcomes (5-minute Apgar score below 7, cord arterial pH, admission to neonatal intensive care unit, and need for endotracheal intubation) were compared between the two treatment methods. Results: Of 361 cesarean deliveries performed at full dilation during the study period, clinicians documented the use of a Fetal Pillow in 91 deliveries and use of the hand-push method in 69. Lower mean intra-operative blood loss ( P  = 0.026), a shorter duration of postpartum hospital admission ( P  = 0.002), and higher mean cord arterial pH ( P  = 0.003) were observed in the Fetal Pillow group. Conclusion: The Fetal Pillow appears to be a safe and effective aid for the delivery of the fetal head during cesarean deliveries at full dilatation.